Rescue mechanisms: UK insolvency law and practice - Pond, Keith (Henry Stewart Talks, 2019)
Rescue mechanisms, Insolvency, Receiverships, Administrations, Creditors, Company Voluntary Arrangement (CVA), Aberystwyth Pier, Pre-pack administration